Informal Caregivers' Well-Being at the Transition to Caregiving. (July 2021) - Williams, Natalie A.; Hatton-Bowers, Holly; Kohel, Kara L.; Pillai, Shruti; Burnfield, Judith M.
The aim of this study was to describe the psychological and physical health needs of informal caregivers in a rehabilitation hospital and explore differences related to informal caregiver and care recipient characteristics. Readiness to engage in health promotion and perspectives on mindfulness meditation were assessed. Informal caregivers ( N = 33) to patients receiving inpatient or outpatient treatment completed the Multidimensional Health Profile screening tools. Readiness to change was assessed using the readiness ruler approach. Almost half of participants (45.5%) had a chronic illness and 18.2% reported that it interferes with daily functioning. Low Positive Health Habits were reported by 43% of participants, and Negative Health Habits were reported by 25%. A subgroup (15%–20%) reported both physical and mental health concerns. A majority of participants indicated it was both very important for them to improve their physical and mental health and felt very confident they could do so. Receptivity to mindfulness meditation was high, with 72.7% reporting an interest. Comprehensive screening and counseling interventions to address the physical and mental health of informal caregivers in physical rehabilitation hospital settings are needed, and information gained from screening could be addressed in interventions delivered by systems-oriented rehabilitation counselors. A mindfulness meditation intervention may be a useful strategy for promoting well-being in this population.